Research of different noise barriers efficiency at different temperature - Vilniškis, Tomas; Januševičius, Tomas (International Conference “Environmental Engineering”, 2017)
In this article was analyzed acoustic efficiency of two different construction noise barriers. Field measurements of noise tests were carried out before and behind a wooden barrier, which height was 2.9 meters and a wooden wall with equipped roof, which height was 3.2 m. As is known the length of the wall, height, surface roughness, shape and material of the wall – key aspects of determining the effectiveness of noise barrier. Different materials, depending on their characteristics of the hard or soft, porous or dense, interact differently with the sound of waves. Article contains research results of noise measurements at positive and negative air temperature. There analyzing wooden noise barrier acoustic efficiency at different temperatures and the effects of temperature to the diffraction of sound waves through the peak of the barrier. Test results show, that noise barrier without structural changes reduced noise level to 14–22 dB, noise barrier with structural changes reduced noise level to 20–23,1 dB, when air temperature was positive. When air temperature was negative, noise barrier without structural changes reduced noise level to 15,5–21,4 dB, noise level with structural changes to 19–26,6 dB.
Keywords: efficiency; noise barrier; temperature; noise level